2006
DOI: 10.1002/jcb.21059
|View full text |Cite
|
Sign up to set email alerts
|

Modeled microgravity stimulates osteoclastogenesis and bone resorption by increasing osteoblast RANKL/OPG ratio

Abstract: Mechanical unloading causes detrimental effects on the skeleton, but the underlying mechanisms are still unclear. We investigated the effect of microgravity on osteoblast ability to regulate osteoclastogenesis. Mouse osteoblast primary cultures were grown for 24 h at unit gravity or under simulated microgravity, using the NASA-developed Rotating Wall Vessel bioreactor. Conditioned media (CM) from osteoblasts subjected to microgravity increased osteoclastogenesis and bone resorption in mouse bone marrow culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 25 publications
2
69
2
Order By: Relevance
“…This hypothesis is supported by our current findings indicating that the bone structure of these subjects is mainly impaired in weight-bearing bone regions. In contrast with constitutional thinness, microgravity bone deficit models display bone uncoupling (41) and a low OPG to RANKL ratio (38), suggesting that this hypothesis must be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by our current findings indicating that the bone structure of these subjects is mainly impaired in weight-bearing bone regions. In contrast with constitutional thinness, microgravity bone deficit models display bone uncoupling (41) and a low OPG to RANKL ratio (38), suggesting that this hypothesis must be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between BMD and BMI in constitutionally thin women suggests a possible direct causality of low body weight on bone density, structure, or strength, as demonstrated in microgravity models with insufficient skeletal load (38,39). The effect of mechanical unloading may be cumulative in constitutionally thin patients because they have a constant low weight during the growth period (12,14,40).…”
Section: Discussionmentioning
confidence: 99%
“…The RWV Bioreactor (model STLV, size 55 ml; Synthecon CELLON S.ar.l, Strassen, Luxembourg) is a horizontal rotating, bubblefree culture vessel with membrane diffusion gas exchange, where the culture medium and the cells on microcarriers rotate inside the vessel with very low fluid stress forces [Duray et al, 1997;Rucci et al, 2002Rucci et al, , 2007Patel et al, 2007]. Microcarriers are in suspension and rotate inside the vessel of the bioreactor as a solid body.…”
Section: Rotating Wall Vessel (Rwv) Bioreactormentioning
confidence: 99%
“…To more deeply dissect these mechanisms, we performed whole genome microarray analysis on primary osteoblasts grown at unit gravity or under simulated microgravity using the NASA-developed rotary cell culture system (RCCS) equipped with a rotating wall vessel (RWV) bioreactor [Duray et al, 1997;Rucci et al, 2002Rucci et al, , 2007Patel et al, 2007]. We identified a subset of genes significantly regulated by microgravity, some of which obviously correlated with osteoblast differentiation and function, while for others no correlation had been found so far with bone metabolism.…”
mentioning
confidence: 99%
“…Then, what will happen to bone cells after being submitted to mechanical unloading caused by weightlessness? In the past few years, people have paid more attention to the function of osteoblasts in responding to weightlessness (Hughes-Fulford et al 2006;Saxena et al 2007;Makihira et al 2008) Scientists have found that after space flight, some changes happen in cell morphology, cell proliferation, cell cycle, cellular cytoskeleton and gene expression in osteoblasts (Landis et al, 2000;Zerath et al 2000;Hughes-Fulford 2001;Doty 2004) Also many studies have investigated the effects of simulated weightlessness on osteoblasts under ground-based condition (Rucci et al 2007;Makihira et al 2008) In recent years, osteocytes have been thought to be as main coordinator responding to mechanical loading in bone tissue (Bonewald 2006(Bonewald , 2007. Osteocytes change their structure and functions after being submitted to mechanical stimulation (Zhang et al 2006;Skerry 2008;Tan et al 2008) Then, is it right that osteocytes also might play important role in responding to mechanical unloading such as weightlessness?…”
Section: Introductionmentioning
confidence: 99%